The status of health science libraries in Laguna - Javier, Mikhaella D.
Health sciences libraries play a vital role as repositories of information in the field of medical and health sciences. In the Philippines, the National Capital Region has the largest number of these libraries, specifically hospital libraries, according to the Department of Health. However, limited information was available regarding the condition of health sciences libraries, especially in areas outside the said region. With this issue, the study sought to determine the status of health science libraries in the province of Laguna, which included their strengths and weaknesses, and their similarities and differences.